Electrocardiographic manifestations of COVID-19: Effect on cardiac activation and repolarization. (September 2021) - Thakore, Avni; Nguyen, James; Pollack, Simcha; Muehlbauer, Stefan; Chi, Benjamin; Knight, Derek; Mehrotra, Bhoomi; Stern, Joshua; Cao, J. Jane; Lucore, Charles; Levine, Joseph
Abstract: Background: Prolonged QT intervals are reported in patients with COVID-19. Additionally, virus particles in heart tissue and abnormal troponin levels have been reported. Consequently, we hypothesize that cardiac electrophysiologic abnormalities may be associated with COVID-19. Methods: This is a retrospective study between March 15 th, 2020 and May 30 th, 2020 of 828 patients with COVID-19 and baseline ECG. Corrected QT (QTc) and QRS intervals were measured from ECGs performed prior to intervention or administration of QT prolonging drugs. QTc and QRS intervals were evaluated as a function of disease severity (patients admitted versus discharged; inpatients admitted to medical unit vs ICU) and cardiac involvement (troponin elevation >0.03 ng/ml, elevated B-natriuretic peptide (BNP) or NT pro-BNP >500 pg/ml). Multivariable analysis was used to test for significance. Odds ratios for predictors of disease severity and mortality were generated. Findings: Baseline QTc of inpatients was prolonged compared to patients discharged (450.1±30.2 versus 423.4±21.7 msec, p <0.0001) and relative to a control group of patients with influenza ( p =0.006). Inpatients with abnormal cardiac biomarkers had prolonged QTc and QRS compared to those with normal levels (troponin - QTc: 460.9±34.6 versus 445.3±26.6 msec, p <0.0001, QRS: 98.7±24.6 vs 90.5±16.9 msec, p <0.0001; BNP - QTc: 465.9±33.0 versus 446.0±26.2 msec, p <0.0001, QRS: 103.6±25.3 versus 90.6±17.6 msec, p <0.0001). Findings were confirmed with multivariable analysis (all p <0.05). QTc prolongation independently predicted mortality (8.3% increase in mortality for every 10 msec increase in QTc; OR 1.083, CI [1.002, 1.171], p =0.04). Interpretation: QRS and QTc intervals are early markers for COVID-19 disease progression and mortality. ECG, a readily accessible tool, identifies cardiac involvement and may be used to predict disease course. Funding: St. Francis Foundation.